2021
DOI: 10.1186/s12889-021-11304-8
|View full text |Cite
|
Sign up to set email alerts
|

Enrolling a rural community pharmacy as a Vaccines for Children provider to increase HPV vaccination: a feasibility study

Abstract: Background Human papillomavirus (HPV) is the most common sexually transmitted infection in the U.S. with over 80 million infected individuals. High-risk strains are associated with 6 different cancers. Although infection is preventable, U.S. vaccination rates remain suboptimal and there are noted disparities between urban and rural communities due to economic barriers, lack of access, and low awareness and education. Methods The current pilot study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Participants in this study trusted pharmacists to provide vaccinations, particularly COVID-19 vaccinations. Past research exploring rural adults’ acceptance of pharmacist-administered immunizations focused on parents’ acceptance of having their adolescent children receive pharmacy-based vaccinations [ 30 , 31 ]. Similar to this study’s findings, previous individuals reported support for pharmacist-administered vaccines due to the convenience of this healthcare delivery approach.…”
Section: Discussionmentioning
confidence: 99%
“…Participants in this study trusted pharmacists to provide vaccinations, particularly COVID-19 vaccinations. Past research exploring rural adults’ acceptance of pharmacist-administered immunizations focused on parents’ acceptance of having their adolescent children receive pharmacy-based vaccinations [ 30 , 31 ]. Similar to this study’s findings, previous individuals reported support for pharmacist-administered vaccines due to the convenience of this healthcare delivery approach.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacies offer a greater degree of territorial equity than other healthcare centers. This is particularly true for inhabitants of backward or difficult-to-access area ( 36 , 37 ), for whom PBI improves accessibility, thus decreasing disparities ( 38 40 ). Second, a better accessibility translates into increased vaccination rates ( 20 , 34 ), particularly in medically underserved populations ( 34 , 38 ) and in adults ( 19 , 41 ).…”
Section: Literature Review: Pharmacy-based Immunizationmentioning
confidence: 99%
“…Moreover, PBI brings profitable business opportunities for pharmacies and policy changes that expand pharmacy services, such as training for pharmacists and pharmacy staff on immunization practices. Several studies have reported improvements in both revenues ( 40 ) and cost-effectiveness of implementing PBI strategies for both, the patients, and the immunization facilities ( 27 ). Singhal and Zhang ( 42 ) claimed that the direct costs per adult influenza and pneumococcal vaccination are lower in pharmacies by 16–26% than in physician offices and other medical settings (11–20%).…”
Section: Literature Review: Pharmacy-based Immunizationmentioning
confidence: 99%
“…19 Barriers to socialdemographic determinants such as lack of coverage may be dealt with through facilitating reimbursement procedures with insurance 43 or through offering vouchers 44 .Trust may also be reinforced through relationship building with the pharmacy team and culturally relevant communication. 29,32,33 Providing convenient modalities for vaccination through walk-in or extended opening hours may reduce accessibility constraints that are frequent in rural areas. 26,45 We identi ed 4 barriers that were common to every vulnerable category.…”
Section: Vulnerability Categoriesmentioning
confidence: 99%